Evaluation of Noah‐MP performance with available soil information for vertically heterogenous soils - Yohannes Tadesse Yimam; Haly L. Neely; Cristine L. S. Morgan; Andrea Kishné; Jonathan Gross; David Gochis (Agrosystems, Geosciences & Environment)
Abstract The increasing availability of modern digital soil databases provides an opportunity to integrate these data into land surface models (LSMs), such as Noah‐MP, for a more realistic representation of soil in estimating mass and energy flux at the land‐atmosphere boundary. Noah‐MP uses a default soil parameter table and a texturally uniform vertical soil profile to a depth of 2 m. Previous research has revised this soil parameter table, and 95% of the values investigated were suggested to be replaced using updated pedotransfer functions and new datasets. In addition to updated parameters, most LSMs do not consider vertical heterogeneity in soil texture despite the widespread distribution of these soils globally. This research assessed both (1) revisions to the soil parameter table and (2) vertical soil heterogeneity, including the presence of bedrock, on simulated water and energy fluxes. At three locations across Texas, plant‐available water (PAW) estimates from Noah‐MP simulations were evaluated using in situ measurements. Due to the lack of water and energy flux data, soil water content values simulated by Noah‐MP were compared with the output from another well‐established model, Root Zone Water Quality Model 2 (RZWQM2). Results showed improving representation of soil improved Nash–Sutcliff efficiency coefficient, model bias, and root mean square difference of Noah‐MP simulated PAW when compared with measured PAW and RZWQM2 simulated PAW. A maximum difference in annual evapotranspiration of 150 mm between simulations was observed. These results demonstrate the need for better accounting of soil knowledge in LSMs for modeling mass and energy exchange at the land‐atmosphere boundaries.